A novel form of transcutaneous electrical nerve stimulation for the reduction of dysesthesias caused by spinal nerve dysfunction: A case series - Nishi, Yuki; Ikuno, Koki; Minamikawa, Yuji; Igawa, Yuki; Osumi, Michihiro; Morioka, Shu (Frontiers in Human Neuroscience, 2022)
Background: Current therapeutic interventions for dysesthesias caused by spinal cord dysfunctions are ineffective. We propose a novel intervention using transcutaneous electrical nerve stimulation (TENS) for dysesthesias and present an in-depth case series. Patients and Methods: Conventional high-frequency TENS and the novel dysesthesia-matched TENS (DM-TENS) were applied to 16 hands (nine patients with spinal cord dysfunction). The dysesthesia-matched TENS' stimulus intensity and frequency matched the intensity and somatosensory profile of the patients' dysesthesias. The Short-Form McGill Pain Questionnaire version-2 (SF-MPQ2) and quantitative sensory testing (QST) were applied during electrical stimulation/no stimulation. We determined intraclass correlation coefficients (ICCs) to evaluate the reliability of the setting and effects on the dysesthesias and the change in subjective dysesthesia between patient’s baseline without TENS and DM-TENS. Results: We were able to apply electrical stimulation matching the patients’ subjective dysesthesia for 14 hands (eight patients). TENS could not be applied for the remaining patient due to severe sensory deficits. Compared to patient’s baseline and high-frequency TENS, the DM-TENS provided significant decreases in tingling/pins-and-needles and numbness on the SF-MPQ2, and it improved the dynamic and static mechanical detection on QST significantly. Regarding the reliability of the dysesthesia-matched TENS settings, the ICCs (1,5) were intensity, 0.95; frequency, 1.00; and effect on dysesthesia, 0.98. Conclusion: DM-TENS improved the dysesthesias and mechanical hypoesthesia caused by spinal cord dysfunction. The effectiveness of DM-TENS particularly for tingling and numbness was clearly higher and was reliable within the patients. These results may suggest an effective treatment of dysesthesias in patients with spinal cord dysfunction.